Evaluasi Kader Pos Kesehatan Pesantren dalam Meningkatkan Perilaku Hidup Bersih dan Sehat pada Santri - Rini Safitri; Erwin Nur Rif'ah; Dewi Rokhmah (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2021)
Background: Poskestrens' cadres as the ambassador in improving Clean and Healthy Life Behavior (CHLB) of the students at boarding school. They also could plan and solve the problems that happened at boarding using any available potential resources. However, the CHLB survey at boarding schools conducted by cadres shows that most students at boarding were not interested in doing the CHLB. This study analyses the determinant factors of Poskestren cadres' behaviour to increase CHLB practice at Islamic boarding schools.Method: This research was quantitative and analytical research with a cross-sectional approach. Sixty-seven Poskestren cadres were selected in this study by using a stratified proportional random sampling technique. Data were collected using a self-administered questionnaire, observation, and documentation. Data were analyzed using univariate, bivariate, and multivariate.Results: The results show that 52.2% of Poskestren cadres had good behavior in improving CHLB at Islamic boarding schools, and the remaining 48.8 were still less behaviour. The Chi-Square statistical test shows no significant relationship between age, education, facilities, infrastructure availability, and the Poskestren cadres' behaviour. However, there was a significant relationship between knowledge, attitudes, encouragement from health workers, motivation from the boarding school caregivers, and the Poskestren cadres' behaviour. The most substantial relationship of this study was the knowledge of Poskestren cadres (p value = 0.000, OR = 16,500). This study suggests that health workers' encouragement by providing virtual-based counseling to the cadres needs to be conducted to improve the Poskestrens cadres' knowledge and attitudes to CHLB.